ÐÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ Ð°ÐºÑ€Ð¾Ð·Ð¸Ð½Ð° Ð² ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÑÐ¿ÐµÑ€Ð¼Ð¸ÑÑ… Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Dunayevskaya, A. V.; Chub, N. N.; Kramar, M. I.; Rodionova, V. L. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2003)
There have been presented the results of the analysis of Â various freezing rates effect on morphological integrity and enzymic activity of human spermatozoa. It has been shown that during freezing with the program and with the rate of 2500Â°C/min the acrosin activity and structural integrity of spermatozoa are kept.